Treat to Target ASCVD Risk with Oral Non-statins and Bempedoic Acid: DELPHI Statement - Sawhney, JPS; Ray, Saumitra; Hazra, Prakash; Sathe, Sunil; Srinivas, B C; Pathak, Vijay; Shah, Jay; Sharma, Kamal; Kakkad, Ashutosh; K, Krishnaprasad (Cardiology and Cardiovascular Medicine, 2023)
Background: In Asian countries, the high endemicity of Coronary Artery Disease (CAD) has been associated with an increase in premature deaths requiring a multi-interventional or multidisciplinary approach to control the cardiovascular risk traits associated with most of these cases. Objective: ESC recommendations on lipid goals of ≤55 mg/dl in Atherosclerotic cardiovascular disease (ASCVD) with or without Type 2 Diabetes Mellitus qualify for a complementary approach with nonstatin in most cases. Bempedoic acid (BA) amongst the non-statins offers differentiated mechanistic to regulate the atherogenic lipids and markers including LDL-C, non-HDL-C, and hs-CRP that may hold relevance in cases with chronic stable angina (CSA) and chronic coronary syndromes (CCS). To further understand the role and relevance of Bempedoic acid as an oral non-statin approach in ASCVD management, a Knowledge, Attitude, and Practices (KAP) survey was conducted between Aug and Oct '22 with 75 HCPs involving a multidisciplinary team with relevant academic and clinical standing on Dyslipidemia management in ASCVD cases across India. Material/Methods: The RAND/UCLA modified Delphi consensusgenerating methodology was used to develop the Statement with Clinical Recommendations on the role of Non-statins and High-intensity statins for the management of ASCVD involving CSA and CCS. The KAP responses were corroborated with literature review and synthesis in the next round of meetings to develop the Delphi Statement based on Agency of Health Care and Quality Systems (AHRQ) criteria for the Strength and Quality of the evidence and experience shared by the specialist panel. Results: Treatment lipid goals for ASCVD as suggested by ESC guidelines remain a clinical challenge with clinical inertia on combination therapy with statins especially for baseline LDL-C levels >/= 120 mg/dl. Nonstatin oral therapy including Bempedoic acid offers differentiated modulation of ATP Citrate Lyase (ACL) & AMP-activated protein kinase (AMPK) pathway unlike ezetimibe (EZE). CLEAR-Harmony, CLEAR-Wisdom, and CLEAR-Outcomes suggest BA offer complementary lipid-lowering, anti-inflammatory and cardioprotective effects in ASCVD cases with T2D, Left Ventricular Dysfunction (LVD), Chronic kidney disease (CKD) (Stage 3b/4) and Peripheral arterial disease (PAD). Conclusion: The Delphi-mediated KAP recommendations provide a reallife approach to the management of ASCVD with non-statins including Bempedoic acid as an initial add-on approach with Moderate or Highintensity statins in outpatient settings of India